A comprehensive review of Quercus semecarpifolia Sm.: An ecologically and commercially important Himalayan tree - Rawat, Balwant; Rawat, Janhvi M.; Purohit, Sumit; Singh, Gajendra; Sharma, Pradeep Kumar; Chandra, Anup; Shabaaz Begum, J. P.; Venugopal, Divya; Jaremko, Mariusz; Qureshi, Kamal A. (Frontiers in Ecology and Evolution, 2022)
Himalayan mountain forests have been a potential candidate for the investigation of perturbations due to the complex geography in which they sustain and the sensitivity of the species toward human disturbance and climate change. Among various tree species, brown oak (Quercus semecarpifolia), a very important component of the Himalayan mountains, has been identified as a keystone species due to its substantial economic and ecological benefits. Maintenance of microclimate and suitable habitats with a rich source of natural resources makes Q. semecarpifolia the most preferred forest for luxuriant growth of ground flora, shelter for fauna, and multipurpose uses by the local people. In a climax community, it plays a critical role in environmental balance both at the local and regional levels. Unfortunately, it has become one of the most overexploited tree species of the Himalayan region over the last few decades due to its high demand for dry season fodder and firewood. The wide range of seedling distribution 348–4,663 individuals ha–1 is evidence of the disturbance accompanied by poor regeneration in Q. semecarpifolia forests. Moreover, litter accumulation and grass cover adversely affect seed germination. The ecological cost of oak forest degradation is perhaps more important and damage is irreversible. Thus, continuous demand and extensive threats accompanied by poor regeneration have drawn the attention of stakeholders to conserve this species. However, propagation protocol, especially the pre-sowing treatment of the species, has not been impressive for large-scale multiplication. This review is comprehensive information on distribution, phenology, regeneration pattern, human threat, conservation approaches, and management of Q. semecarpifolia in the Himalayan region.